Transformational Leadership in the Digital Age: Adaptive Strategies in Higher Education Institutions - Mulyadi Mulyadi; Akhsanul In’am; Khozin Khozin (AL-ISHLAH: Jurnal Pendidikan, 2025)
The accelerating pace of digital transformation poses significant leadership challenges in higher education, particularly in developing countries with limited infrastructure and hierarchical cultures. Transformational leadership is increasingly recognized as a key factor in enabling strategic adaptation and innovation in this context. This study employed a qualitative phenomenological approach to explore how transformational leadership facilitates digital innovation in higher education institutions. Data were collected through in-depth interviews with 36 participants—including academic leaders, faculty members, and students—across three universities in Indonesia with varying levels of digital readiness. Thematic analysis was used to identify patterns and meanings in participant experiences. Findings reveal that transformational leadership—characterized by visionary direction, participatory governance, and empowerment—plays a critical role in fostering a collaborative digital culture. Leadership practices emphasizing transparency, inclusion, and emotional support reduced resistance to change and enhanced faculty and student engagement. Cross-unit collaboration, contextual training, and adaptive strategies further contributed to sustainable innovation. This study highlights the socio-cultural nuances of digital leadership in resource-constrained settings, demonstrating both the potential and limitations of transformational leadership in higher education digitalization. The findings contribute to leadership theory and offer practical guidance for institutions navigating digital change.